Abiotic contexts consistently influence mycorrhiza functioning independently of the composition of synthetic arbuscular mycorrhizal fungal communities - Voříšková, Alena; Jansa, Jan; Püschel, David; Vosátka, Miroslav; Šmilauer, Petr; Janoušková, Martina (Mycorrhiza, 2019)
The relationship between mycorrhiza functioning and composition of arbuscular mycorrhizal (AM) fungal communities is an important but experimentally still rather little explored topic. The main aim of this study was thus to link magnitude of plant benefits from AM symbiosis in different abiotic contexts with quantitative changes in AM fungal community composition. A synthetic AM fungal community inoculated to the model host plant Medicago truncatula was exposed to four different abiotic contexts, namely drought, elevated phosphorus availability, and shading, as compared to standard cultivation conditions, for two cultivation cycles. Growth and phosphorus uptake of the host plants was evaluated along with the quantitative composition of the synthetic AM fungal community. Abiotic context consistently influenced mycorrhiza functioning in terms of plant benefits, and the effects were clearly linked to the P requirement of non-inoculated control plants. In contrast, the abiotic context only had a small and transient effect on the quantitative AM fungal community composition. Our findings suggest no relationship between the degree of mutualism in AM symbiosis and the relative abundances of AM fungal species in communities in our simplified model system. The observed progressive dominance of one AM fungal species indicates an important role of different growth rates of AM fungal species for the establishment of AM fungal communities in simplified systems such as agroecosystems.
Keywords: mykorhiza; Phosphorus; Symbiosis; Mycorrhizae; mykobiom; Medicago truncatula; fosfor; období sucha; symbióza; Droughts; Mycobiome; sluneční záření; Sunlight